Meminimalisir Waste Pada Proses Produksi Sarung Tangan Golf Menggunakan Lean Six Sigma - Agam Setianandha; Ari Zaqi Al-Faritsy (CV. KAMPUS AKADEMIK PUBLISING, 2024)
CV.XYZ is a business that produces golf gloves in Yogyakarta Special Region. In the production process, several wastes were identified, including defects of 24,746 units out of a total of 365,568 units. Defective products can trigger inappropriate processing waste, the rework process requires 176.1 seconds/pcs. Waste waiting and transportation were identified due to 24 transportation activities with a total time of 323.10 seconds and a distance of 161 meters. This study aims to identify the causes of waste and recommend improvements using the Lean Six Sigma method. It is known that the CV. XYZ sigma performance level is 3.62 sigma and Current VSM data shows VA activities of 46% (655.86 seconds), NVA 39% (556.57 seconds), NNVA 15% (219.94 seconds), and lead time 1,432.37 seconds. To prevent product defects and reduce inappropriate processing waste, an SOP was created for tailoring. Recommendations for improvement to minimize waste transportation and waiting are to rearrange the layout of the sewing, semi-finishing, and finishing areas. After the improvement, VA activity increased to 64% (655.86 seconds), NVA decreased to 14% (142.24 seconds), and NNVA increased to 22% (219.94 seconds).